Linking shock textures revealed by BSE, CL, and EBSD with U-Pb data (LA-ICP-MS and SIMS) from zircon from the Araguainha impact structure, Brazil - Hauser, Natalia; Reimold, Wolf Uwe; Cavosie, Aaron J.; Crósta, Alvaro P.; Schwarz, Winfried H.; Trieloff, Mario; Souza, Carolinna Da Silva Maia de; Pereira, Luciana A.; Rodrigues, Eduardo N.; Brown, Matthews (Meteoritics & planetary science, 2019)
A silicious impact melt rock from polymict impact breccia of the northern part of the alkali granite core of the Araguainha impact structure, central Brazil, has been investigated. The melt rock is thought to represent a large mass of impact-generated melt in suevite. In particular, a diverse population of zircon grains, with different impact-induced microstructures, has been analyzed for U-Pb isotopic systematics. Backscattered electron and cathodoluminescence images reveal heterogeneous intragrain domains with vesicular, granular, vesicular plus granular, and vesicular plus (presumably) baddeleyite textures, among others. The small likely baddeleyite inclusions are not only preferentially located along grain margins but also occur locally within grain interiors. LA-ICP-MS U-Pb data from different domains yield lower intercept ages of 220, 240, and 260 Ma, a result difficult to reconcile with the previous “best age” estimate for the impact event at 254.7 ± 2.7 Ma. SIMS U-Pb data, too, show a relatively large range of ages from 245 to 262 Ma. A subset of granular grains that yielded concordant SIMS ages were analyzed for crystallographic orientation by EBSD. Orientation mapping shows that this population consists of approximately micrometer-sized neoblasts that preserve systematic orientation evidence for the former presence of the high-pressure polymorph reidite. In one partially granular grain (#36), the neoblasts occur in linear arrays that likely represent former reidite lamellae. Such grains are referred to as FRIGN zircon. The best estimate for the age of the Araguainha impact event from our data set from a previously not analyzed type of impact melt rock is based on concordant SIMS data from FRIGN zircon grains. This age is 251.5 ± 2.9 Ma (2σ, MSWD = 0.45, p = 0.50, n = 4 analyses on three grains), indistinguishable from previous estimates based on zircon and monazite from other impact melt lithologies at Araguainha. Our work provides a new example of how FRIGN zircon can be combined with in situ U-Pb geochronology to extract an accurate age for an impact event.
Gesehen am 30.06.2021